2017
DOI: 10.1186/s12885-017-3746-y
|View full text |Cite
|
Sign up to set email alerts
|

YRNA expression predicts survival in bladder cancer patients

Abstract: BackgroundNon-coding RNAs play an important role in human carcinogenesis. YRNAs (Ro-associated Y), a novel class of non-coding RNAs, have been identified as biomarker in various malignancies, but remain to be studied in urinary bladder cancer (BCA) patients.MethodsThe expression of all four YRNAs (RNY1, RNY3, RNY4, RNY5) was determined in archival BCA (urothelial carcinoma, n = 88) and normal urothelial bladder (n = 30) tissues using quantitative real-time PCR. Associations with clinicopathological parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 26 publications
(38 reference statements)
1
39
1
Order By: Relevance
“…No additional studies were identified by a manual search of the references of the original studies. Finally, the remaining 37 articles were eligible for the systematic review (Wang et al, 2006 ; He et al, 2013 , 2016a , b ; Fan et al, 2014 ; Li et al, 2014 , 2017 ; Srivastava et al, 2014 ; Yan et al, 2014 ; Chen et al, 2015 , 2017 ; Eissa et al, 2015a , b ; Milowich et al, 2015 ; Zhao F. J. et al, 2015 ; Zhao X. L. et al, 2015 ; Duan et al, 2016 ; Iliev et al, 2016 ; Zhan et al, 2016a , b , 2017a , b ; Zhang et al, 2016 , 2017 ; Cao et al, 2017 ; Cui et al, 2017 ; Dudek et al, 2017 ; Du et al, 2017 ; Hu Y. Y. et al, 2017 ; Liao et al, 2017 ; Lin et al, 2017 ; Tolkach et al, 2017 ; Wu et al, 2017 ; Xiong et al, 2017 ; Yang et al, 2017 ; Ye et al, 2017 ; Zhuang et al, 2017 ), including 26 studies for clinicopathological parameters, 19 studies for prognosis, and 7 studies for diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No additional studies were identified by a manual search of the references of the original studies. Finally, the remaining 37 articles were eligible for the systematic review (Wang et al, 2006 ; He et al, 2013 , 2016a , b ; Fan et al, 2014 ; Li et al, 2014 , 2017 ; Srivastava et al, 2014 ; Yan et al, 2014 ; Chen et al, 2015 , 2017 ; Eissa et al, 2015a , b ; Milowich et al, 2015 ; Zhao F. J. et al, 2015 ; Zhao X. L. et al, 2015 ; Duan et al, 2016 ; Iliev et al, 2016 ; Zhan et al, 2016a , b , 2017a , b ; Zhang et al, 2016 , 2017 ; Cao et al, 2017 ; Cui et al, 2017 ; Dudek et al, 2017 ; Du et al, 2017 ; Hu Y. Y. et al, 2017 ; Liao et al, 2017 ; Lin et al, 2017 ; Tolkach et al, 2017 ; Wu et al, 2017 ; Xiong et al, 2017 ; Yang et al, 2017 ; Ye et al, 2017 ; Zhuang et al, 2017 ), including 26 studies for clinicopathological parameters, 19 studies for prognosis, and 7 studies for diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, an observed HR > 1 implied that the patients with increased lncRNAs expression had a worse survival. Increased expressions of MALAT1 (Fan et al, 2014 ; Li et al, 2017 ), ASAP1-IT1 (Yang et al, 2017 ), SPRY4-IT1 (Zhao X. L. et al, 2015 ), TUG1 (Iliev et al, 2016 ), lncRNA-n336928 (Chen et al, 2015 ), GHET1 (Li et al, 2014 ), linc-UBC1 (He et al, 2013 ), YRNA5 (Tolkach et al, 2017 ), XIST (Hu Y. Y. et al, 2017 ), PVT1 (Cui et al, 2017 ), and SNHG16 (Cao et al, 2017 ) were significantly correlated with poor prognosis in OS, along with decreased expressions of CAT1297 (Dudek et al, 2017 ), lncRNA-LET, YRNA1 (Tolkach et al, 2017 ), YRNA3 (Tolkach et al, 2017 ), YRNA4 (Tolkach et al, 2017 ), and NBAT1 (Du et al, 2017 ). It was worth noting that the most significant association was observed between increased expressions of SPRY4-IT1 and poor OS (HR = 3.716; 95% CI: 2.084–6.719; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify if full-length RNY4 might be responsible for the differential expression detected by small RNA-seq, not validated by RT-PCR specific from RNY4-5 ′ F, we quantified the full-length RNY4 in 12 ALCL and 12 HD plasmatic exosomes by qRT-PCR using primers from Tolkach et al (63). The full-length RNY4 was significantly more abundant in ALCL than in HD (Mann Whitney, p = 0.017) (Figure 2A).…”
Section: Genuine Mirna-like Rny4 Fragments or Full-length Rny4?mentioning
confidence: 99%
“…YRNAs are recognized as a component of soluble ribonucleoproteins (RNPS). These are related with many pathological conditions [ 100 ]. The Ro60 protein bound to the YRNAs controls the fate of the misfolded RNAs.…”
Section: Yrnasmentioning
confidence: 99%